Positive electrode active material for secondary battery, and secondary battery

By using lithium metal composite oxide with an Fm-3m crystal structure and appropriate microcrystal size as the positive electrode active material in the lithium-ion secondary battery, the problem of insufficient capacity improvement in the prior art is solved, and a secondary battery with high energy density and high capacity utilization is realized.

CN119698700APending Publication Date: 2025-03-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380056034.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-06-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, the positive electrode active material of lithium ion secondary battery is insufficient in improving capacity, and there is still room for improvement.

Method used

A lithium metal composite oxide having a crystal structure that can be attributed to the spatial group Fm-3m is used as the positive electrode active material. The oxide contains at least Li and Mn, and its crystallite size is controlled to be in the range of 1 nm to 100 nm.

Benefits of technology

By optimizing the crystal structure and microcrystal size of lithium metal composite oxides, a high-energy density secondary battery is achieved and capacity utilization efficiency is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005255763700000091
    Figure BDA0005255763700000091
  • Figure BDA0005255763700000101
    Figure BDA0005255763700000101
  • Figure HDA0005255763710000011
    Figure HDA0005255763710000011
Patent Text Reader

Abstract

A positive electrode active material for a secondary battery, the positive electrode active material containing a lithium metal composite oxide having a crystal structure attributable to space group Fm-3m, the lithium metal composite oxide containing at least Li and Mn, and the crystallite size of the lithium metal composite oxide being in the range of 1-100 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a secondary battery and a secondary battery. Background Art

[0002] Secondary batteries, particularly lithium ion secondary batteries, are expected to be used as power sources for small consumer applications, power storage devices, and electric vehicles because of their high output power and high energy density. As the positive electrode active material of a lithium ion secondary battery, a composite oxide of lithium and a transition metal (e.g., cobalt) is used. By replacing a part of cobalt with nickel, high capacity can be achieved.

[0003] On the other hand, in recent years, in response to the requirement for high energy density, Li-excess type lithium metal composite oxides based on Li 1+x Mn 1-x O2 having a rock salt structure have attracted attention.

[0004] Patent Document 1 discloses a positive electrode active material having a crystal structure belonging to the space group Fm-3m and containing a lithium transition metal composite oxide represented by the composition formula Li 1+x Nb y Me z A p O2 (Me is a transition metal containing Fe and / or Mn, 0 < x < 1, 0 < y < 0.5, 0.25 ≤ z < 1, A is an element other than Nb and Me, 0 ≤ p ≤ 0.2, provided that Li 1+p Fe 1-q Nb q O2 and 0.15 < p ≤ 0.3, 0 < q ≤ 0.3 are excluded).

[0005] Prior Art Documents

[0006] Patent Document 1: Japanese Patent No. 6197029 Specification Summary of the Invention

[0007] In Patent Document 1, high capacity can be achieved by controlling the composition (i.e., adding Nb). However, the effect of improving the capacity is insufficient, and there is still room for improvement.

[0008] In view of the above circumstances, one aspect of the present disclosure relates to a positive electrode active material for a secondary battery, which includes a lithium metal composite oxide having a crystal structure belonging to the space group Fm-3m, the lithium metal composite oxide containing at least Li and Mn, and the microcrystal size of the lithium metal composite oxide being in the range of 1 nm to 100 nm.

[0009] Another embodiment of the present disclosure relates to a positive electrode active material for a secondary battery, which includes a lithium metal composite oxide having a crystal structure that can be attributed to the space group Fm-3m, wherein the lithium metal composite oxide contains at least Li and Mn, and the half-value width of the diffraction peak attributed to the (200) plane in the X-ray diffraction (XRD) diagram using CuKα rays of the lithium metal composite oxide is in the range of 0.1° to 1.8° based on 2θ.

[0010] Still another aspect of the present disclosure relates to a secondary battery including a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode, wherein the positive electrode includes the positive electrode active material for a secondary battery.

[0011] The novel features of the present disclosure are set forth in the appended claims, but the present disclosure in both aspects of constitution and content, combined with other objects and features of the present disclosure, will be more fully understood through the following detailed description with reference to the accompanying drawings.

[0012] According to the present disclosure, a secondary battery with high energy density can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a schematic perspective view of a secondary battery according to an embodiment of the present disclosure, with a portion thereof cut away. DETAILED DESCRIPTION

[0014] Hereinafter, the embodiments of the present disclosure are illustrated, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes illustrated, but other numerical values ​​and materials can also be applied as long as the effects of the present disclosure can be obtained. In this specification, the record of "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read alternatively as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values ​​related to specific physical properties, conditions, etc. are illustrated, as long as the lower limit does not become above the upper limit, any one of the illustrated lower limits and any one of the illustrated upper limits can be arbitrarily combined. When multiple materials are illustrated, one can be selected and used alone, or two or more can be used in combination.

[0015] In addition, the present disclosure includes a combination of matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the accompanying claims. In other words, matters recorded in two or more claims arbitrarily selected from the plurality of claims recorded in the accompanying claims may be combined as long as no technical contradiction arises.

[0016] In the following description, the term "comprising" or "including" includes "comprising (or including)", "consisting essentially of" and "consisting of".

[0017] The secondary battery includes at least a non-aqueous electrolyte secondary battery such as a lithium ion battery and a lithium metal secondary battery.

[0018] The positive electrode active material for a secondary battery of an embodiment of the present disclosure comprises a lithium metal composite oxide having a crystal structure attributable to the space group Fm-3m. The lithium metal composite oxide comprises at least Li and Mn, and the crystallite size of the lithium metal composite oxide is in the range of 1 nm to 100 nm. The crystallite size of the lithium metal composite oxide is preferably less than 80 nm, more preferably less than 60 nm. The crystallite size of the lithium metal composite oxide is preferably greater than 4 nm, more preferably greater than 5 nm or greater than 6 nm. The upper and lower limits of the above crystallite size can be arbitrarily combined.

[0019] The crystallite size is calculated based on the Scherrer formula from the half-peak width of the diffraction peak attributable to the (200) plane in the X-ray diffraction (XRD) diagram of the lithium metal composite oxide using CuKα radiation. In the X-ray diffraction (XRD) diagram of the lithium metal composite oxide using CuKα radiation, the half-peak width of the diffraction peak attributable to the (200) plane of the positive electrode active material for secondary batteries can also be in the range of 0.1° to 1.8° based on 2θ.

[0020] In general, the capacity of lithium metal composite oxides is improved when the crystallite size is large and the crystal structure is fully developed. On the other hand, it is believed that the small lithium metal composite oxide with a crystallite size of less than 100nm significantly increases the effect of promoting the release and absorption of lithium ions caused by the increase in the surface area of ​​the crystal boundary, thereby improving the capacity.

[0021] The lithium metal composite oxide has a crystal structure based on a rock salt structure belonging to the space group Fm-3m. That is, the lithium metal composite oxide has a crystal structure similar to the rock salt structure belonging to the space group Fm-3m. The lithium metal composite oxide has a crystal structure based on a rock salt structure represented by, for example, NaCl, and can have a structure in which oxygen atoms are arranged at anion sites, and Li atoms and metal atoms other than Li are irregularly arranged at cation sites.

[0022] The lithium metal composite oxide preferably contains Mn as a transition metal element. The molar ratio of Mn in the lithium metal composite oxide may also be greater than the molar ratio of the transition metal element or metal elements other than Mn. The ratio b / c of ​​the number of atoms b of Mn in the lithium metal composite oxide to the number of atoms c of the metal element M other than Li and Mn may also be 1 or more and 12 or less.

[0023] The lithium metal composite oxide may be a composite oxide based on a composite oxide of Li and Mn. Examples of such a composite oxide of Li and Mn include Li in excess 1+x Mn 1-x O2 or Li 1+x Mn 1-x-y M y It is believed that in the case of a crystal structure similar to a rock salt structure belonging to the Li-excess space group Fm-3m, the effect of improving the capacity by reducing the crystallite size to 100 nm or less is greater than in the case of a crystal structure clearly belonging to the space group Fm-3m.

[0024] Lithium metal composite oxides may also contain fluorine (F). In the above crystal structure, fluorine can replace oxygen atoms at anion sites. As a result, the state of excess Li is stabilized, and a higher capacity can be obtained. In addition, by replacing fluorine atoms, the average discharge potential increases. Furthermore, the state of excess Li refers to a state in which the number of Li atoms in the composite oxide is greater than the number of transition metal atoms.

[0025] In the above-mentioned lithium metal composite oxide, since the configuration of Li at the cation site is irregular and the binding state of Li is various, the voltage distribution accompanying Li release has a wide amplitude. Therefore, it is difficult to use the lower part of the low potential side of the voltage distribution as capacity. However, by introducing fluorine atoms, the voltage distribution accompanying Li release moves to the high potential side, so it becomes easy to use the lower part as capacity. Thus, the available capacity is further increased.

[0026] As the lithium metal composite oxide, for example, a composition formula of Li a Mn b M c O d F e (wherein, 1≤a≤1.4, 0.5≤b≤0.9, 0≤c≤0.4, 1.33≤d≤2, 0≤e≤0.67, 1.7≤d+e≤2) is satisfied. Here, M contains at least one element other than Li and Mn. d+e may be less than 1.94, or less than 1.9 or less than 1.8.

[0027] As shown in the above composition formula, part of the oxygen atoms in the anion site can also be replaced by fluorine atoms. As a result, the state of excess Li (a>1) is stabilized and a high capacity can be obtained. In addition, as mentioned above, the average discharge potential rises and the available capacity is further increased.

[0028] The lithium metal composite oxide may also contain an element M other than Li and Mn. The element M may contain at least one selected from Fe, Ge, Si, Ga, Ni, Co, Sn, Cu, Nb, Mo, Bi, V, Cr, Y, Ti, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, Ta, W, La, Ce, Pr, Gd, Sm, Eu, Yb, Dy and Er. Among them, the lithium metal composite oxide preferably contains at least one selected from Ni, Sn, Mo, W, Ta and Zn as the metal element M.

[0029] The lithium metal composite oxide may also contain Ti as an element M other than Li and Mn. Ti has the effect of increasing the capacity of the lithium metal composite oxide having the above-mentioned crystal structure. The reason for this is not yet clear, but one of the reasons is that in the lithium metal composite oxide, Ti is replaced by Ti with empty d orbitals. 4+ The lithium metal composite oxide exists in the form of Mn, so the highly symmetrical rock salt structure is easy to become stable, and the rock salt structure can be stabilized even after repeated charge and discharge. In the case where the lithium metal composite oxide contains Ti, the ratio of the number of Mn atoms to the number of Ti atoms in the lithium metal composite oxide, i.e., Mn / Ti, is preferably 7 or more.

[0030] A mixture of raw materials of elements constituting lithium metal composite oxides can also be calcined to obtain lithium metal composite oxides. By calcining, the growth of crystals similar to the rock salt structure belonging to the space group Fm-3m is promoted to obtain a lithium metal composite oxide with a large crystallite size. Thereafter, by implementing a pulverization treatment, the crystallite size can be controlled within the range of 1nm to 100nm. As raw materials of elements constituting lithium metal composite oxides, lithium manganate (LiMnO2) and oxides of element M can be used. Li2O and Mn2O3 can also be used as raw materials. As a fluorine source, lithium fluoride (LiF) can be used.

[0031] Next, the secondary battery according to the embodiment of the present disclosure is described in detail. The secondary battery includes, for example, the following positive electrode, negative electrode, electrolyte, and separator.

[0032] [positive electrode]

[0033] The positive electrode comprises: a positive electrode collector, and a positive electrode mixture layer formed on the surface of the positive electrode collector and containing a positive electrode active material. As the positive electrode, the above-mentioned positive electrode for secondary battery is used. The positive electrode mixture layer can be formed, for example, by applying a positive electrode slurry obtained by dispersing a positive electrode mixture containing a positive electrode active material, a binder, etc. in a dispersion medium to the surface of the positive electrode collector and drying it. The dried coating film can also be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode collector or on both surfaces.

[0034] The positive electrode mixture layer contains a positive electrode active material as an essential component, and may contain a binder, a thickener, a conductive agent, a positive electrode additive, etc. as optional components. As the binder, the thickener, and the conductive agent, known materials can be used.

[0035] As a positive electrode active material, the above-mentioned lithium metal composite oxide having a crystal structure similar to a rock salt structure belonging to the space group Fm-3m is included. The composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The particle size of the primary particles is generally 0.01μm to 1μm. The average particle size of the composite oxide is, for example, 1μm to 50μm, preferably 2μm to 25μm. Here, the average particle size of the composite oxide refers to the median diameter (D50) at which the frequency is accumulated to 50% in the volume-based particle size distribution, which is measured by a laser diffraction particle size distribution measuring device. The D10 diameter of the composite oxide (the diameter at which the frequency is accumulated to 10% in the volume-based particle size distribution) can also be less than 0.6μm.

[0036] The BET surface area of ​​the composite oxide is preferably between 0.01 m 2 / g~15m 2 / g range.

[0037] The content of the elements constituting the composite oxide can be measured by an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.

[0038] As the positive electrode active material, other known lithium metal oxides other than the above-mentioned lithium metal composite oxides may be mixed with the above-mentioned lithium metal composite oxides having a crystal structure similar to the above-mentioned rock salt structure. Examples of other lithium metal oxides include Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1- b M b O c , Li a Mn2O4、Li a Mn 2-b M bLithium transition metal composite oxides such as LiO4, LiMePO4, Li2MePO4F, etc. Here, M is at least one selected from Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B. Me contains at least a transition element (for example, contains at least one selected from Mn, Fe, Co, Ni). Here, 0≤a≤1.2, 0≤b≤0.9, 2.0≤c≤2.3. Furthermore, the value a representing the molar ratio of lithium increases or decreases according to charge and discharge.

[0039] The shape and thickness of the positive electrode current collector can be selected based on the shape and range of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0040] [negative electrode]

[0041] The negative electrode comprises, for example, a negative electrode current collector and a negative electrode active material layer formed on the surface of the negative electrode current collector. The negative electrode active material layer can be formed, for example, by applying a negative electrode slurry formed by dispersing a negative electrode mixture containing a negative electrode active material, a binder, etc. in a dispersion medium to the surface of the negative electrode current collector and drying it. The dried coating film can also be rolled as needed. In other words, the negative electrode active material can also be a mixture layer. In addition, lithium metal foil or lithium alloy foil can also be attached to the negative electrode current collector. The negative electrode active material layer can be formed on one surface of the negative electrode current collector or on both surfaces.

[0042] The negative electrode active material layer contains the negative electrode active material as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as optional components. As the binder, the conductive agent, and the thickener, known materials can be used.

[0043] The negative electrode active material includes a material that electrochemically absorbs and releases lithium ions, lithium metal and / or lithium alloy. As a material that electrochemically absorbs and releases lithium ions, a carbon material, an alloy material, etc. are used. As a carbon material, for example, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be exemplified. Among them, graphite with excellent charge and discharge stability and low irreversible capacity is preferred. As an alloy material, a material containing at least one metal that can form an alloy with lithium can be listed, and silicon, tin, silicon alloys, tin alloys, silicon compounds, etc. can be listed. Silicon oxide, tin oxide, etc. combined with oxygen can also be used.

[0044] As an alloy-based material containing silicon, for example, a lithium-ion conductive phase and a silicon composite material in which silicon particles are dispersed in the lithium-ion conductive phase can be used. As the lithium-ion conductive phase, for example, a silicon oxide phase, a silicate phase, and / or a carbon phase can be used. The main component (e.g., 95 to 100% by mass) of the silicon oxide phase can be silicon dioxide. Among them, a composite material composed of a silicate phase and silicon particles dispersed in the silicate phase is preferable in terms of high capacity and low irreversible capacity.

[0045] The silicate phase can contain, for example, at least one selected from Group 1 elements and Group 2 elements of the long-period type periodic table. As the Group 1 element of the long-period type periodic table and the Group 2 element of the long-period type periodic table, for example, lithium (Li), potassium (K), sodium (Na), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), etc. can be used. As other elements, aluminum (Al), boron (B), lanthanum (La), phosphorus (P), zirconium (Zr), titanium (Ti), etc. can also be contained. Among them, a lithium-containing silicate phase (hereinafter also referred to as a lithium silicate phase) is preferable because of its small irreversible capacity and high initial charge-discharge efficiency.

[0046] The lithium silicate phase only needs to be an oxide phase containing lithium (Li), silicon (Si), and oxygen (O), and other elements can also be contained. For example, the atomic ratio of O to Si, i.e., O / Si, in the lithium silicate phase is greater than 2 and less than 4. Preferably, O / Si is greater than 2 and less than 3. For example, the atomic ratio of Li to Si, i.e., Li / Si, in the lithium silicate phase is greater than 0 and less than 4. The lithium silicate phase can have a composition represented by the formula Li 2z SiO 2+z (0 < z < 2). z preferably satisfies the relationship of 0 < z < 1, and more preferably z = 1 / 2. As elements other than Li, Si, and O that can be contained in the lithium silicate phase, for example, iron (Fe), chromium (Cr), nickel (Ni), manganese (Mn), copper (Cu), molybdenum (Mo), zinc (Zn), aluminum (Al), etc. can be cited.

[0047] The carbon phase can be composed of, for example, low-crystallinity amorphous carbon (i.e., non-crystalline carbon). The amorphous carbon can be, for example, hard carbon, soft carbon, or other carbon.

[0048] As the negative electrode current collector, a non-porous conductive substrate (such as a metal foil) or a porous conductive substrate (such as a mesh body, a net body, a perforated plate, etc.) is used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified.

[0049] [Electrolyte]

[0050] The electrolyte includes a solvent and a solute dissolved in the solvent. The solute is an electrolyte salt that undergoes ion dissociation in the electrolyte. The solute may include, for example, a lithium salt. The components of the electrolyte other than the solvent and the solute are additives. The electrolyte may include various additives. The electrolyte is usually used in a liquid state, but may also be in a state where fluidity is restricted by a gelling agent or the like.

[0051] The solvent uses an aqueous solvent or a non-aqueous solvent. As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, chain carboxylates, etc. can be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), vinylene carbonate (VC), etc. can be listed. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be listed. In addition, as cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be listed. As chain carboxylates, methyl acetate, ethyl acetate, propyl acetate, methyl propionate (MP), ethyl propionate (EP), etc. can be listed. The non-aqueous solvent can be used alone or in combination of two or more.

[0052] Examples of the nonaqueous solvent include cyclic ethers, chain ethers, nitriles such as acetonitrile, and amides such as dimethylformamide.

[0053] Examples of cyclic ethers include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, propylene oxide, 1,2-butylene oxide, 1,3-dioxolane, Alkane, 1,4-di Alkane, 1,3,5-tri Alkanes, furans, 2-methylfuran, 1,8-cineole, crown ethers, etc.

[0054] Examples of the chain ethers include 1,2-dimethoxyethane, dimethyl ether, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ether, dihexyl ether, ethyl vinyl ether, butyl vinyl ether, methyl phenyl ether, ethyl phenyl ether, butyl phenyl ether, pentyl phenyl ether, methoxytoluene, benzyl ethyl ether, diphenyl ether, dibenzyl ether, o-dimethoxybenzene, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, 1,1-dimethoxymethane, 1,1-diethoxyethane, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0055] These solvents may be fluorinated solvents in which part of hydrogen atoms are replaced by fluorine atoms. Fluorinated ethylene carbonate (FEC) may also be used as the fluorinated solvent.

[0056] As the lithium salt, for example, a lithium salt containing chloric acid (LiClO4, LiAlCl4, LiB10 Cl 10 etc.), lithium salts of fluorinated acids (LiPF6, LiPF2O2, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated acid imides (LiN(FSO2)2, LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.

[0057] The concentration of the lithium salt in the electrolyte may be 1 mol / liter or more and 2 mol / liter or less, or 1 mol / liter or more and 1.5 mol / liter or less. By controlling the lithium salt concentration within the above range, an electrolyte having excellent ion conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above description.

[0058] The electrolyte may contain other known additives. Examples of the additives include 1,3-propane sultone, toluene sulfonate, cyclohexylbenzene, biphenyl, diphenyl ether, and fluorobenzene.

[0059] [Diaphragm]

[0060] The separator is between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, microporous films, woven fabrics, non-woven fabrics, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.

[0061] As an example of the structure of a secondary battery, an electrode group in which a positive electrode and a negative electrode are wound across a separator and a structure in which a nonaqueous electrolyte is contained in an outer casing can be cited. Alternatively, it is also possible to replace the wound electrode group with an electrode group in which a positive electrode and a negative electrode are stacked across a separator, and other electrode groups such as a stacked electrode group can be applied. The secondary battery can also be, for example, any of a cylindrical, square, coin-shaped, button-shaped, laminated type, etc.

[0062] Figure 1 This is a partially cutaway schematic perspective view of a rectangular secondary battery according to an embodiment of the present disclosure.

[0063] The battery comprises: a battery case 4 with a square bottom, an electrode group 1 housed in the battery case 4, and a non-aqueous electrolyte (not shown). The electrode group 1 comprises: a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator between them. The negative electrode collector of the negative electrode is electrically connected to the negative terminal 6 provided on the sealing plate 5 via the negative electrode lead 3. The negative terminal 6 is insulated from the sealing plate 5 by a resin gasket 7. The positive electrode collector of the positive electrode is electrically connected to the back of the sealing plate 5 via the positive electrode lead 2. That is, the positive electrode is electrically connected to the battery case 4 which also serves as the positive terminal. The periphery of the sealing plate 5 is fitted with the open end of the battery case 4, and the fitting portion is laser welded. The sealing plate 5 has an injection hole for the non-aqueous electrolyte, which is blocked by the sealing plug 8 after the injection.

[0064] Furthermore, the structure of the secondary battery may be cylindrical, coin-shaped, button-shaped, etc., with a metal battery case, or may be a laminated battery with a battery case made of a laminate sheet, i.e., a laminated body of a barrier layer and a resin sheet. In the present disclosure, the type, shape, etc. of the secondary battery are not particularly limited.

[0065] Postscript

[0066] The following techniques are disclosed through the description of the above embodiments.

[0067] (Technology 1)

[0068] A positive electrode active material for a secondary battery, comprising a lithium metal composite oxide having a crystal structure attributable to a space group Fm-3m,

[0069] The lithium metal composite oxide contains at least Li and Mn,

[0070] The crystallite size of the lithium metal composite oxide is in the range of 1 nm to 100 nm.

[0071] (Technique 2)

[0072] According to the secondary battery positive electrode active material of technology 1, the crystallite size of the lithium metal composite oxide is 80 nm or less.

[0073] (Technique 3)

[0074] According to the secondary battery positive electrode active material of technology 1, the crystallite size of the lithium metal composite oxide is 60 nm or less.

[0075] (Technique 4)

[0076] A positive electrode active material for a secondary battery, comprising a lithium metal composite oxide having a crystal structure attributable to a space group Fm-3m,

[0077] The lithium metal composite oxide contains at least Li and Mn,

[0078] In the X-ray diffraction (XRD) pattern using CuKα rays of the lithium metal composite oxide, the half-value width of the diffraction peak attributed to the (200) plane is in the range of 0.1° to 1.8° based on 2θ.

[0079] (Technique 5)

[0080] According to any one of techniques 1 to 4, the ratio b / c of ​​the number of atoms b of Mn to the number of atoms c of the metal element M other than Li and Mn in the lithium metal composite oxide is 1 or more and 12 or less.

[0081] (Technique 6)

[0082] According to any one of techniques 1 to 5, the secondary battery positive electrode active material, wherein the lithium metal composite oxide contains fluorine.

[0083] (Technique 7)

[0084] The secondary battery positive electrode active material according to any one of techniques 1 to 6, wherein the lithium metal composite oxide has a composition formula Li a Mn b M c O d F e (wherein, M contains at least one element other than Li and Mn, and satisfies 1≤a≤1.4, 0.5≤b≤0.9, 0≤c≤0.4, 1.33≤d≤2, 0≤e≤0.67, 1.7≤d+e≤2).

[0085] (Technology 8)

[0086] According to the positive electrode active material for secondary batteries described in Technology 7, the element M contains at least one selected from Fe, Ge, Si, Ga, Ni, Co, Sn, Cu, Nb, Mo, Bi, V, Cr, Y, Ti, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, Ta, W, La, Ce, Pr, Gd, Sm, Eu, Yb, Dy and Er.

[0087] (Technique 9)

[0088] A secondary battery comprises a positive electrode, a negative electrode, an electrolyte and a separator between the positive electrode and the negative electrode.

[0089] The positive electrode includes the positive electrode active material for a secondary battery according to any one of Techniques 1 to 8.

[0090] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.

[0091] <Example 1>

[0092] [Production of positive electrode]

[0093] The lithium metal composite oxide is composed of Li 1.22 Mn 0.61 Ti 0.175 O 1.87 Manganese oxide (Mn2O3), lithium carbonate (Li2CO3) and titanium oxide (TiO2) were mixed at a predetermined mass ratio and the mixture was calcined at 950°C for 10 hours to obtain a lithium metal composite oxide.

[0094] The composition of the sintered lithium metal composite oxide was identified by ICP emission analysis. In addition, the oxygen content was evaluated using an oxygen-nitrogen analyzer (HORIBA EMGA-920). 1.22 Mn 0.61 Ti 0.175 O 1.78 , the oxygen content ratio is lower than when adding material.

[0095] The sintered lithium metal composite oxide was put into a planetary ball mill (Premium-Line P7 manufactured by Fritsch, rotation speed: 300 rpm, container: 45 mL, balls: φ3 mm Zr balls), and treated in an Ar atmosphere and at room temperature for 12 hours (the cycle of stopping for 10 minutes after running for 1 hour was set to 12 times), thereby obtaining a lithium metal composite oxide with a predetermined composition.

[0096] The obtained lithium metal composite oxide was measured and analyzed by using a powder X-ray diffraction device using CuKα rays. The result confirmed that the composite oxide had a crystal structure based on a rock salt type belonging to the space group Fm-3m based on the number and peak position of the XRD peaks. In addition, the half-peak width of the diffraction peak attributable to the (200) plane of the composite oxide was obtained. The crystallite size was obtained based on the half-peak width based on the Scherrer formula.

[0097] The obtained lithium metal composite oxide, acetylene black and polyvinylidene fluoride were mixed at a solid content mass ratio of 7:2:1, and N-methyl-2-pyrrolidone (NMP) was used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to a positive electrode core composed of aluminum foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to obtain a positive electrode.

[0098] [Preparation of electrolyte]

[0099] A non-aqueous electrolyte was prepared by adding LiPF6 as a lithium salt to a mixed solvent in which ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were mixed at a predetermined volume ratio.

[0100] [Production of test unit]

[0101] A test unit was prepared using the positive electrode and a negative electrode counter electrode including lithium metal foil. The positive electrode and the negative electrode counter electrode were arranged relative to each other through a separator to form an electrode body, and the electrode body was housed in a coin-shaped outer can. After injecting electrolyte into the outer can, the outer can was sealed to obtain a coin-shaped test secondary battery A1.

[0102] <Examples 2 to 8, Comparative Example 1>

[0103] In Example 1, the conditions (rotation speed and processing time) for pulverizing the sintered lithium metal composite oxide using a planetary ball mill were changed as shown in Table 1. Otherwise, a test cell was prepared in the same manner as in Example 1 to obtain secondary batteries A1 to A8 of Examples 2 to 8.

[0104] Furthermore, a test cell was produced by using a sintered lithium metal composite oxide that was not subjected to the planetary ball mill treatment but was pulverized in a mortar, thereby obtaining a secondary battery B1 of Comparative Example 1.

[0105] <Comparative Example 2>

[0106] The lithium metal composite oxide is composed of Li 1.07 Mn 0.8 Ti 0.133 Manganese oxide (Mn2O3), lithium carbonate (Li2CO3) and titanium oxide (TiO2) were mixed at a predetermined mass ratio of 200 g / min to 100 g / min of O2, and the mixture was calcined at 1050°C for 10 hours to obtain a lithium metal composite oxide.

[0107] A test cell was produced using the sintered lithium metal composite oxide that was pulverized in a mortar without being processed by a planetary ball mill, thereby obtaining a secondary battery B2 of Comparative Example 2.

[0108] <Examples 9 to 23>

[0109] The raw materials of each element constituting the lithium metal composite oxide were mixed at a predetermined mass ratio so as to form the charge composition shown in Table 2. As the raw materials of each element, oxides of each element (CoO, NiO, Fe2O3, TiO2, MgO, respectively) were used as the Co raw material, Ni raw material, Fe raw material, Ti raw material, and Mg raw material. In addition, lithium fluoride (LiF) was used as the F raw material.

[0110] The sintered lithium metal composite oxide was put into a planetary ball mill (Premium-Line P7 manufactured by Fritsch, rotation speed: 300 rpm, container: 45 mL, balls: φ3 mm Zr balls), and treated in an Ar atmosphere and at room temperature for 12 hours (the cycle of stopping for 10 minutes after running for 1 hour was set to 12 times), thereby obtaining a lithium metal composite oxide with a predetermined composition.

[0111] Using the obtained lithium metal composite oxide, a test cell was prepared in the same manner as in Example 1, thereby obtaining secondary batteries A9 to A23 of Examples 9 to 23.

[0112] In Examples 2 to 23 and Comparative Examples 1 and 2, the X-ray diffraction pattern of the composite oxide after sintering (and after ball milling as needed) was measured and analyzed by using a powder X-ray diffraction device using CuKα rays. According to the number and peak positions of the XRD peaks, it was confirmed that the composite oxide had a crystal structure based on a rock salt type belonging to the space group Fm-3m. In addition, the half-peak width of the diffraction peak attributable to the (200) plane of the composite oxide was calculated. The crystallite size was calculated based on the half-peak width based on the Scherrer formula.

[0113] [evaluate]

[0114] (Initial discharge capacity)

[0115] The secondary battery was charged at a constant current of 0.1C at room temperature until the battery voltage reached 4.95V, and then charged at a constant voltage of 4.95V until the current reached 0.01C. Thereafter, the battery was stopped for 20 minutes, and constant current discharge was performed at a constant current of 0.1C until the battery voltage reached 2.5V, and the discharge capacity was measured. The discharge capacity per unit mass of the positive electrode active material (lithium metal composite oxide) was obtained as the initial discharge capacity C0.

[0116] For batteries A1 to A8 of Examples 1 to 8 and batteries B1 and B2 of Comparative Examples, the evaluation results of the initial discharge capacity C0 are shown in Table 1 together with the charge composition of the lithium metal composite oxide used as the positive electrode active material in each battery, the conditions during sintering, the conditions during ball milling, the half-maximum width (FWHM) of the XRD diffraction peak attributed to the (200) plane, and the crystallite size.

[0117] For batteries A9 to A23 of Examples 9 to 23, the evaluation results of the initial discharge capacity C0 are shown in Table 2 together with the charge composition of the lithium metal composite oxide used as the positive electrode active material in each battery, the half-maximum width (FWHM) of the XRD diffraction peak attributed to the (200) plane, and the crystallite size.

[0118] As shown in Tables 1 and 2, Batteries A1 to A23 in which the crystallite size of the lithium metal composite oxide is in the range of 1 nm to 100 nm have improved initial discharge capacities compared to Batteries B1 and B2.

[0119] Table 1

[0120]

[0121] Table 2

[0122]

[0123] Industrial Applicability

[0124] According to the secondary battery of the present disclosure, a secondary battery having high capacity and excellent cycle characteristics can be provided. The secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0125] Although the present invention has been described using the present preferred embodiments, this disclosure should not be interpreted as limiting. Various modifications and changes will be unambiguous and clear to those of ordinary skill in the art to which the present disclosure belongs by reading the above disclosure. Therefore, the appended claims should be interpreted as including all modifications and changes without departing from the true spirit and scope of the present disclosure.

[0126] Description of Reference Numerals

[0127] 1: electrode group, 2: positive electrode lead, 3: negative electrode lead, 4: battery case, 5: sealing plate, 6: negative electrode terminal, 7: gasket, 8: sealing plug.

Claims

1. A positive electrode active material for a secondary battery, A lithium metal composite oxide having a crystal structure attributable to space group Fm-3m, The lithium metal composite oxide contains at least Li and Mn, The crystallite size of the lithium metal composite oxide is in the range of 1 nm to 100 nm. 2 . The positive electrode active material for a secondary battery according to claim 1 , wherein the crystallite size of the lithium metal composite oxide is 80 nm or less. 3 . The positive electrode active material for a secondary battery according to claim 1 , wherein the crystallite size of the lithium metal composite oxide is 60 nm or less.

4. A positive electrode active material for a secondary battery, A lithium metal composite oxide having a crystal structure attributable to space group Fm-3m, The lithium metal composite oxide contains at least Li and Mn, The lithium metal composite oxide has an XRD pattern, that is, an X-ray diffraction pattern using CuKα rays, in which the half-value width of a diffraction peak attributable to the (200) plane is in the range of 0.1° to 1.8° based on 2θ. 5 . The secondary battery positive electrode active material according to claim 1 , wherein a ratio b / c of ​​the number of atoms b of Mn to the number of atoms c of the metal element M other than Li and Mn in the lithium metal composite oxide is 1 or more and 12 or less. 6 . The positive electrode active material for a secondary battery according to claim 1 , wherein the lithium metal composite oxide contains fluorine.

7. The positive electrode active material for a secondary battery according to any one of claims 1 to 4, The lithium metal composite oxide has a composition formula of Li a Mn b M c O d F e express, in, M includes at least one element other than Li and Mn, and satisfies 1≤a≤1.4, 0.5≤b≤0.9, 0≤c≤0.4, 1.33≤d≤2, 0≤e≤0.67, and 1.7≤d+e≤2.

8. The positive electrode active material for a secondary battery according to claim 7, The element M includes at least one selected from Fe, Ge, Si, Ga, Ni, Co, Sn, Cu, Nb, Mo, Bi, V, Cr, Y, Ti, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, Ta, W, La, Ce, Pr, Gd, Sm, Eu, Yb, Dy and Er.

9. A secondary battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator between the positive electrode and the negative electrode, The positive electrode comprises the positive electrode active material for a secondary battery according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Formation of coated film

    JP1986097029A